1993
DOI: 10.1002/per.2410070203
|View full text |Cite
|
Sign up to set email alerts
|

Personal and environmental factors contributing to parenting stress among employed and nonemployed women

Abstract: Over the past 20 years, significantly more women have returned to the workforce after the birth of their child. Despite gains made by the second women's movement and attendant socio‐political changes, women continue to bear the major parenting responsibilities in addition to household chores. Does this additional role of workforce member result in a more highly stressed mother? This study recruited 120 mothers of infants and toddlers from a range of occupations who provided information on their adjustment to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Analyses were also run to determine whether or not there was a moderated mediation effect using participant employment status as a dichotomous moderator to determine consistency with previous findings reported in the literature. Similar to previous research indicating that employment status in and of itself is not a significant predictor of parenting stress (Forgays & Forgays, 1993; Warfield, 2001), results of a moderated mediation analysis of the current sample using a MODMED test following the Preacher, Rucker, and Hayes (2007) approach indicated that participants’ employment status ( employed or not employed ) did not significantly moderate the effects of mindfulness on parenting stress or of parenting stress on parental responsiveness…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Analyses were also run to determine whether or not there was a moderated mediation effect using participant employment status as a dichotomous moderator to determine consistency with previous findings reported in the literature. Similar to previous research indicating that employment status in and of itself is not a significant predictor of parenting stress (Forgays & Forgays, 1993; Warfield, 2001), results of a moderated mediation analysis of the current sample using a MODMED test following the Preacher, Rucker, and Hayes (2007) approach indicated that participants’ employment status ( employed or not employed ) did not significantly moderate the effects of mindfulness on parenting stress or of parenting stress on parental responsiveness…”
Section: Resultssupporting
confidence: 81%
“…Parenting stress can occur in any circumstance but, based on this model, is more likely when resources are lacking. That being said, parental employment status has been shown to not be a singular predictor of parenting stress (Forgays & Forgays, 1993; Warfield, 2001). Overwhelming research on mindfulness has established its relation to decreased stress levels (Kabat-Zinn, 2003).…”
mentioning
confidence: 99%
“…Muslow and colleagues (2002) found that partner support lowered stress for mothers with young children. Similarly, the effects of employment on parenting stress are moderated by individual and contextual factors, such as depression and financial strain (Forgays & Forgays, 1993; Gyamfi, Brooks-Gunn, & Jackson, 2001). …”
Section: Literature Reviewmentioning
confidence: 99%